Technological man‐made disaster precondition phase model for major accidents - Shaluf, Ibrahim M.; Ahmadun, Fakharul‐razi; Mat Said, Aini; Mustapha, Sa’ari; Sharif, Rashid (Emerald, 2002)
Major hazard organizations are dealing with hazardous material exceeding the threshold quantity. Major hazard organizations are relatively secure areas and cannot fail from single error. However, failure of an organization to control hazardous material usually results in a technological man‐made disaster. The conditions preceding the onset of technological man‐made disaster are collectively called the technological man‐made disaster precondition phase “incubation period”. A model has been developed representing the technological man‐made disaster pre‐condition phase where it focuses on the origin of the technological man‐made disaster. The model was based on detailed analysis of four technological man‐made disasters at major hazard installations in Malaysia.